Feasibility of Bronchial Washing Fluid‐Based Approach to Early‐Stage Lung Cancer Diagnosis. (29th April 2019) - Ryu, Jeong‐Seon; Lim, Jun Hyeok; Lee, Myoung Kyu; Lee, Seung Jae; Kim, Hyun‐Jung; Kim, Min Jeong; Park, Mi Hwa; Kim, Jung Soo; Nam, Hae‐Seong; Park, Nuri; Yong, Seok Joong
Abstract: A blood‐based approach such as circulating tumor DNA remains challenging in diagnosis for early‐stage disease. Bronchial washing (BW) is a minimally invasive procedure that yields fluids that may contain tumor DNA. Therefore, we prospectively enrolled 12 patients with early‐stage non‐small cell lung cancer without endoscopically visible tumors. Somatic mutations were analyzed using ultra‐deep next‐generation sequencing in 48 paired specimens (primary tumor tissue, normal tissue, BW supernatant, and BW precipitate). In primary tumors, 130 missense mutations/indels (5–16 per patient) and 20 driver mutations (0–3 per patient) were found. Concordance of driver mutations between BW fluids and primary tumors was 95.0%. The allele frequencies for missense mutations/indels in BW supernatants significantly correlated with those in primary tumors and were higher than those in BW precipitates. These findings suggest that BW supernatants are reflective of tumor‐associated mutations and could be used for early‐stage lung cancer diagnosis. Abstract : The potential of circulating tumor DNA (ctDNA) detection in early stage lung cancer is explored. This study investigated whether bronchial washing, a minimally invasive procedure that yields fluids that may contain ctDNA, can reflect genetic profiles of primary tumors using next‐generation sequencing.